Effects of Helicobacter pylori Infection on the Oral Microbiota of Reflux Esophagitis Patients - Liang, Tian; Liu, Fang; Liu, Lijun; Zhang, Zhiying; Dong, Wenxue; Bai, Su; Ma, Lifeng; Kang, Longli (Frontiers in Cellular and Infection Microbiology, 2021)
The human oral microbiota plays a vital role in maintaining metabolic homeostasis. To explore the relationship between Helicobacter pylori (Hp) and reflux esophagitis, we collected 86 saliva samples from reflux esophagitis patients (RE group) and 106 saliva samples from healthy people (C group) for a high-throughput sequencing comparison. No difference in alpha diversity was detected between the RE and the C groups, but beta diversity of the RE group was higher than the C group. Bacteroidetes was more abundant in the RE group, whereas Firmicutes was more abundant in the C group. The linear discriminant analysis effect size analysis demonstrated that the biomarkers of the RE group were Prevotella, Veillonella, Leptotrichia, and Actinomyces, and the biomarkers of the C group were Lautropia, Gemella, Rothia, and Streptococcus. The oral microbial network structure of the C group was more complex than that of the RE group. Second, to explore the effect of Hp on the oral microbiota of RE patients, we performed the 14C-urea breath test on 45 of the 86 RE patients. We compared the oral microbiota of 33 Hp-infected reflux esophagitis patients (REHpp group) and 12 non-Hp-infected reflux esophagitis patients (REHpn group). No difference in alpha diversity was observed between the REHpn and REHpp groups, and beta diversity of the REHpp group was significantly lower than that of the REHpn group. The biomarkers in the REHpp group were Veillonella, Haemophilus, Selenomonas, Megasphaera, Oribacterium, Butyrivibrio, and Campylobacter; and the biomarker in the REHpn group was Stomatobaculum. Megasphaera was positively correlated with Veillonella in the microbial network of the REHpp group. The main finding of this study is that RE disturbs the human oral microbiota, such as increased beta diversity. Hp infection may inhibit this disorderly trend.